2017
DOI: 10.14740/jocmr3066w
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cognitive Impairment in Patients on 3-Hydroxy-3-Methyl-Glutaryl-CoA Reductase Inhibitors

Abstract: BackgroundAtherosclerotic cardiovascular diseases are the leading cause of death in the United States. A reduction in cholesterol with 3-hydroxy-3-methyl-glutaryl-CoA reductase inhibitors (statin) significantly reduces mortality and morbidity. Statins may be associated with cognitive impairment or dementia. Our aim was to study the association of cognitive impairment or dementia in patients who were on a statin.MethodsElectronic medical records of 3,500 adult patients in our suburban internal medicine office w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 63 publications
3
15
0
3
Order By: Relevance
“…It appears to be the reason why atorvastatin and simvastatin have higher association with non-hepatocytic adverse effects, such as cognitive impairment, compared to all other lipophilic statins [51,54]. Our findings of higher association of cognitive impairment with lipophilic atorvastatin were aligned with the other studies that have demonstrated higher association and severity of cognitive impairment with lipophilic statins compared with hydrophilic statins [11,21,46,[59][60][61][62].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…It appears to be the reason why atorvastatin and simvastatin have higher association with non-hepatocytic adverse effects, such as cognitive impairment, compared to all other lipophilic statins [51,54]. Our findings of higher association of cognitive impairment with lipophilic atorvastatin were aligned with the other studies that have demonstrated higher association and severity of cognitive impairment with lipophilic statins compared with hydrophilic statins [11,21,46,[59][60][61][62].…”
Section: Discussionsupporting
confidence: 84%
“…As early as in 1997, there have been implications of statin therapy with cognitive behavioral changes, such as increased violence [23]. Since then, there has been increasing data from case reports, various retrospective and prospective studies, which ultimately lead to the FDA formally recognizing that statins may cause cognitive impairment [7,9,11,19,23,46]. Muldoon et al have done multiple studies that tested attention, reaction time, and psychomotor speed of those on statins [7,9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations